2021
DOI: 10.3389/fimmu.2020.622772
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PTX3 in Mineralization Processes and Aging-Related Bone Diseases

Abstract: The Long Pentraxin 3 (PTX3) is a multifunctional glycoprotein released by peripheral blood leukocytes and myeloid dendritic cells in response to primary pro-inflammatory stimuli, that acts as a non-redundant component of the humoral arm of innate immunity. In addition to the primary role in the acute inflammatory response, PTX3 seems to be involved in other physiological and pathological processes. Indeed, PTX3 seems to play a pivotal role in the deposition and remodeling of bone matrix during the mineralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…An interesting observation is the lack of association between the presence of plaque calcifications and hs-CRP blood level. Indeed, our and other studies demonstrated that the plaque calcification is an active process that can be modulated by the inflammation [16,18,[34][35][36][37], as occur in the physiological bone mineralization [38,39]. This evidence suggests that the calcification of the carotid plaque could be related to specific inflammatory cytokines [25,37] rather than to a specific low-grade inflammatory state.…”
Section: Discussionsupporting
confidence: 57%
“…An interesting observation is the lack of association between the presence of plaque calcifications and hs-CRP blood level. Indeed, our and other studies demonstrated that the plaque calcification is an active process that can be modulated by the inflammation [16,18,[34][35][36][37], as occur in the physiological bone mineralization [38,39]. This evidence suggests that the calcification of the carotid plaque could be related to specific inflammatory cytokines [25,37] rather than to a specific low-grade inflammatory state.…”
Section: Discussionsupporting
confidence: 57%
“…In other age-related contexts, PTX3 seems to play a pivotal role in the deposition and remodelling of bone matrix during the mineralization process, promoting osteoblasts differentiation and activity, suggesting a pivotal role in the pathophysiology of age-related bone diseases, such as osteoporosis, both in mice and humans [77]. Furthermore, given its involvement in bone metabolism, several studies agree with the definition of PTX3 as a molecule significantly involved in the pathogenesis of age-related bone diseases, such as osteoporosis, both in mice and humans.…”
Section: Ptx3 As a Possible Link Between Inflammation Cancer And Agingmentioning
confidence: 99%
“…The study of novel mediators of bone metabolism is essential to understand the physiological responses of bone tissue to microgravity. In this regard, pentraxin 3 (PTX3) has recently been proposed as a new potential therapeutic target and diagnostic marker for the treatment of age-related bone diseases, given its known involvement in physiological and pathophysiological processes occurring in bone tissue, including bone matrix deposition and remodelling during the mineralization process, calcification formation and fracture healing [ 14 ]. Specifically, Scimeca et al observed that primary cultures of osteoblasts from osteoporotic patients undergoing hip arthroplasty for fragility fracture showed a low capacity to form hydroxyapatite micro-crystals and a reduced expression of PTX3 in contrast to control cells characterized by numerous hydroxyapatite micro-crystals and a high expression of PTX3 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%